2022
DOI: 10.3389/fnmol.2022.1015220
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling reveals mitochondrial dysfunction in the cerebellum of transgenic mice overexpressing DYRK1A, a Down syndrome candidate gene

Abstract: IntroductionDYRK1A is a dual-specificity kinase that is overexpressed in Down syndrome (DS) and plays a key role in neurogenesis, neuronal differentiation and function, cognitive phenotypes, and aging. Dyrk1A has also been implicated in cerebellar abnormalities observed in association with DS, and normalization of Dyrk1A dosage rescues granular and Purkinje cell densities in a trisomic DS mouse model. However, the underlying molecular mechanisms governing these processes are unknown.MethodsTo shed light on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…It will also be interesting to test whether increased levels of DYRK1A might interfere with the feedback loop and thus impact on mitochondrial protein biogenesis. The discovery of the DYRK1A-TOM70 axis as regulatory hub that links the main mitochondrial protein import pathways now paves the way to reach a mechanistic understanding of the described links of Down syndrome and dysfunctional mitochondrial energy metabolism 70 , 71 .…”
Section: Discussionmentioning
confidence: 99%
“…It will also be interesting to test whether increased levels of DYRK1A might interfere with the feedback loop and thus impact on mitochondrial protein biogenesis. The discovery of the DYRK1A-TOM70 axis as regulatory hub that links the main mitochondrial protein import pathways now paves the way to reach a mechanistic understanding of the described links of Down syndrome and dysfunctional mitochondrial energy metabolism 70 , 71 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that the mouse cerebellum exhibited active oxidative phosphorylation and mitochondrial malfunction the overexpression of dual-specificity tyrosine phosphorylation regulated kinase 1A (DYRK1A), a dual-specificity kinase that was upregulated in DS and aging. This report indicated that in DS, DYRK1A targeted mitochondria and induced cell senescence [117]. Cell senescence was observed in pregnancies complicated by PE, fetal growth restriction, preterm birth, and DS.…”
Section: Adverse Pregnancy Outcomes and Excessive Cell Senescence At ...mentioning
confidence: 99%